(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Health problems of elderly are an emerging health burden throughout the world. Bangladesh is currently undergoing a demographic transition and the proportion of the population of 60 years and older is increasing rapidly. Health care providers and policymakers are highly concerned with this burning issue. Objective: To know the disease pattern among the elderly patients in Combined Military Hospital, Dhaka. Materials and Methods: This cross-sectional study was carried out from July 2015 to June 2016 among 152 elderly patients above 60 years of age admitted in Combined Military Hospital (CMH), Dhaka Cantonment. Data were collected by face-to-face interview with semi-structured questionnaire and checklist following purposive sampling technique. Analysis of data was done by Statistical Package for Social Science (SPSS, version 20.0). Results: Mean age of the elderly was 72.06±4.56 years with the range of 60-80 years and majority (90.8%) of the elderly was male. Out of total 152 elderly patients, by occupation majority (31.6%) were in the business group followed by 30.3% in the retired group and 9.2 % in the housewife group. Average monthly family income was BDT 17927.63±7360.75 with the range of BDT 6000-35000. With initial complaints elderly patients reported to doctors in private chamber (38.2%), private hospital (25.6%) and Govt hospital (5.9%). Among all of the elderly patients, majority (21.1%) had Diabetes Mellitus followed by Rheumatoid Arthritis (17.6%), Asthma (12.5%), Cataract (11.2%), ENT problem (6.6%), Malignancy (5.9%) and Benign Enlargement of Prostate 8(5.3%). Conclusion: The number of elderly people is expanding rapidly; it also presents multifaceted health problems and thus creates unique challenges for the national healthcareservices. Early identification of problem and ensuring the availability of health with economic and social support can have a control over the elderly health problems. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 8-12